Centralisation of Public Diplomacy Management in China: The Carrefour Incident - Оксана Александровна Тимофеева (Communications. Media. Design, 2017)
The article deals with the use of public diplomacy tools for promoting the interests of the state. The main purpose of this paper is to show the public diplomacy potential possibilities to achieve policy goals in an authoritarian one-party state with a focus on the online environment. As an example, we selected the Carrefour Incident, a conflict that occurred in China during the preparations for the Olympic Games in Beijing in 2008. The conflict broke out between the Chinese citizens, who were offended by the reaction of the Government of France towards the actions of pro-Tibetan activists during the Olympic torch relay in Paris, and the Carrefour Group in China.The introduction provides a brief history of the development of the concept of public diplomacy in the context of Nicholas Сull’s theory as well as explores several media communications models and theories that are helpful in better understanding the details of the case. Subsequently, the article presents a detailed chronology and the stages of the conflict and describes the main actors’ goals and actions. The conflict was initially supported by the government via social networking sites and soft propaganda techniques, and when this goal was achieved, it was effectively pacified through Internet audience management tools. The case demonstrates approaches to implicit information management and shares some techniques to identify the critical phases of the conflict using basic media statistics. The Chinese experience is important for understanding the effectiveness of the media control policy and conflict management for state actors and non-governmental organisations. The conclusion provides a number of theoretical and practical points about the nature of this conflict and consolidating role of the Internet in it. In particular, some parts of the conclusion concern the effectiveness of Chinese “soft power” and the necessity of a term base transformation.